INTERGRANULAR CORROSION AND DUCTILE-BRITTLE TRANSITION BEHAVIOUR IN MARTENSITIC STAINLESS STEEL - Gunawan Gunawan; Amir Arifin (Indonesian Journal of Engineering and Science (IJES), 2021)
Material mechanical behavior is critical for both safety and economic considerations. Because engineering items are manufactured using appropriate grade materials, mechanical approval of the materials used must be completed before assembly. Petrochemicals, marine, and biomaterials are just a few of the industries that use stainless steel. Despite its extensive use, structural failure is still frequently caused by inadequate stainless steel type selection. As a result, dangerous conditions, resulting in personal harm or financial loss. Dangerous conditions is might result in accidents, resulting in personal injury or financial loss. Martensite stainless steel is a type of stainless steel with a high strength value but is brittle, necessitating careful handling. Intergranular corrosion, sensitization, tempering heat treatment, and the Ductile to Brittle Transition Temperature (DBTT) are topics still working on Martensite stainless steel for researchers.